Investigating behavioural addictions in adults with and without attention deficit hyperactivity disorder - James L. Findon; Annika Muck; Beáta Tóthpál- Davison; Eleanor J. Dommett (PLoS ONE, 2025)
Attention deficit hyperactivity disorder (ADHD) confers greater risk of alcohol and substance use disorders, which may be linked to altered compulsivity and impulsivity within the condition. However, no study has investigated the link between these constructs and behavioural addictions in ADHD. The aim of this study was to investigate whether individuals with ADHD show increased impulsivity, compulsivity, and associated distress, as well as addictive behaviour for gambling, exercise, and internet use, and to assess the relationship between these factors. Adults with and without ADHD were recruited from across the UK and completed an online survey measuring impulsivity, compulsivity, gambling, internet use and exercise addiction. Three hundred and forty-six adults took part (Healthy control = 137, ADHD-medicated = 110, ADHD-unmedicated = 99). Those declaring a diagnosis of ADHD reported greater internet use problems and greater withdrawal from exercise. Medicated individuals also reported higher exercise continuance and were more likely be symptomatic for exercise dependency. Individuals identifying with ADHD had greater levels of impulsivity and compulsivity, with impulsivity correlated with all behavioural addictions, whilst compulsivity correlated only with exercise and internet use. Regression analyses indicated that the distress caused by impulsivity and compulsivity was associated with internet use. Although further research is needed, this study indicates that the greater risk of behavioural addictions found in those with ADHD may relate to impulsivity and compulsivity, and that this should be considered when managing ADHD.